NIIF para las PYMES: ¿La solución al problema para la aplicación de la normativa internacional? - Molina Llopis, Rafael (Pontificia Universidad Católica del Perú, 2014)
The IFRS for SMEs is of the size of its scope, a key player in the international accounting harmonization process. After a brief reference to the IASB’s role in this process, this paper makes a description of the steps followed for the issuance of IFRS for SMEs and their relevant characteristics, to continue with a comparative analysis of the main differences with full IFRS. Finally, the document contains some reflections related to the practical difficulties facing the process of implementing international standards and possible solutions, according to the author, be considered.